2008
DOI: 10.1097/olq.0b013e3181573d84
|View full text |Cite
|
Sign up to set email alerts
|

HIV and STD Status Among MSM and Attitudes About Internet Partner Notification for STD Exposure

Abstract: Overall, this study documents broad acceptance of Internet PN by at-risk MSM, regardless of HIV serostatus, including a willingness to receive or initiate PN-related e-mail. If public health officials consider using Internet notification services, they may need to anticipate and address concerns of HIV-infected MSM, and will need to use a culturally-sensitive, social marketing campaign to ensure that those who may benefit from these services are willing to use this modality for PN. Internet PN should be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 23 publications
0
25
2
Order By: Relevance
“…For example, the finding that Internet users were no more or less likely to be generative versus non-generative seeds suggests that while the Internet may be useful for HIV prevention and education activities [38][39][40][41] as well as for public health functions such as partner notification, 42,43 it may not be the a Comparisons were made between generative and non-generative seeds using Chi-square global tests of independence and Fisher's exact tests where cell sizes were small. Median group differences were calculated using Wilcoxon rank-sum test statistics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the finding that Internet users were no more or less likely to be generative versus non-generative seeds suggests that while the Internet may be useful for HIV prevention and education activities [38][39][40][41] as well as for public health functions such as partner notification, 42,43 it may not be the a Comparisons were made between generative and non-generative seeds using Chi-square global tests of independence and Fisher's exact tests where cell sizes were small. Median group differences were calculated using Wilcoxon rank-sum test statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Of the six studies reviewed [7,39,[42][43][44][45], only one found that prevalence of lifetime STD was significantly lower among API men (13%) compared to White (32%), Black (26%), and Latino (29%) [7]. All three studies conducted in San Francisco found similar rates of STDs across races/ethnicities [39,42,43].…”
Section: Do Api Msm Have Lower Rates Of Sexually Transmitted Diseasesmentioning
confidence: 51%
“…Of the 11 studies reviewed, none found that API men were more likely to have ever been tested for HIV or are tested more frequently than other MSM [7,13,17,39,44,[46][47][48][49][50][51].…”
Section: Do Api Msm Have Lower Rates Of Sexually Transmitted Diseasesmentioning
confidence: 99%
“…There are four different approaches to notifying sexual partners of clients infected with an STI or HIV: provider referral (notification of sexual partners via a third party, such as an individuals' medical provider), partner referral (notification of sexual partners via the index client), contract referral (an agreement between the client and provider, where the client is given the opportunity to notify their sexual partners on their own, with the understanding that their partners will be notified by a third party if they have not been notified by a predetermined date), and dual referral (both the client and provider notify the clients' sexual partners together) (CDC 1998a, b;Mathews et al 2002;Mimiaga et al 2007aMimiaga et al , 2008a.…”
Section: Introductionmentioning
confidence: 99%